Demographic and economic factors that affect the fatality rate produced by the SARS-COV-2 virus worldwide - Illescas, Eymy (2021)
This study aims to identify the economic and demographic determinants that affect the fatality rate from COVID-19 in the periods of 90, 120 and 150 days after the first appearance of the virus in the territory. The analysis is presented in two stages, in the first, a Cluster analysis is used with the K-means methodology in which 210 countries from all continents are used and they are classified into four groups: i. Countries infected very quickly with a relatively high growth rate of contagion and low lethality, ii. Countries infected rapidly with a very high growth rate of contagion and lethality, iii. Countries infected slowly with a relatively high growth rate of contagion and a relatively low lethality and iv. Countries infected very slowly with a growth rate of contagion and low fatality In the second stage, the groups established in the first stage are used and OLS or Tobit models are estimated, depending on the presence or not of a Limited Dependent Variable in the fatality rate by COVID-19. The independent variables are the contagion growth rate, the severity index and the underlying conditions of the countries directly related to COVID-19 such as access to drinking water, hospital beds per 10,000 inhabitants, government efficacy index, population over 65 years and economic growth rate.